Campus Teaching PGSD STKIP Darussalam Cilacap Students at SD Ciporos 6 - Shoimatun Febriyani; Febri Isnawati (Universitas Sebelas Maret, 2022)
This study aims to describe the implementation of the Merdeka Curriculum through the Teaching Campus of PGSD STKIP Darussalam Cilacap students at Ciporos 6 Elementary School. The research method used is descriptive qualitative with observation, interview, and documentation techniques as data collection tools. Respondents in this study were students from the Teaching Campus and teachers at Ciporos 6 Elementary School. The results showed that the implementation of the Merdeka Curriculum through the Teaching Campus of PGSD STKIP Darussalam Cilacap students at Ciporos 6 Elementary School had gone well. Teaching Campus students have succeeded in integrating Pancasila values and character in learning and increasing learning creativity and innovation. Teachers at Ciporos 6 Elementary School responded positively and fully supported the implementation of the Independent Curriculum through the Teaching Campus.